Perbedaan Model Pembelajaran Index Card Match Dengan Learning Station Rotation Pada Hasil Belajar Siswa - Ratu Meri Agusta; Yuyu Yuhana (Sumule Indonesia Publishing, 2025)
This study aims to compare the effectiveness of the Index Card Match and Learning Station Rotation learning models on students' learning outcomes in Pancasila Education, specifically concerning the topic of Practicing Pancasila Values in Daily Life. The subjects of this study were 30 sixth-grade students at SDN Cipondoh Makmur. A descriptive qualitative approach was employed, with data collected through observation, achievement tests, and document analysis. Each learning model was implemented over two meetings with different treatments. The observation results indicated that both models increased student engagement, although the Learning Station Rotation model created a more varied and collaborative learning atmosphere. The achievement test results showed that students taught using the Learning Station Rotation model had a higher average score (86.2) compared to those trained with the Index Card Match model (80.4). Although the difference was not statistically significant, the findings suggest that the Learning Station Rotation model tends to be more effective in enhancing students’ conceptual understanding and learning motivation. Therefore, both models can serve as alternative active learning strategies that are relevant to Pancasila Education in primary schools.